1995
DOI: 10.2307/30105091
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian Hemodialysis Catheter Infections: A Prospective, Randomized Trial of an Attachable Silver-Impregnated Cuff for Prevention of Catheter-Related Infections

Abstract: Multiple presumed predictor variables for catheter-related infections, exit site infection rate, bacteremia rates, and semiquantitative cultures of all catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The positive results of these earlier studies made routine use of silver-coated megaprostheses possible in our department. Since negative results with silver-coated devices have also been reported in the literature [10,11,25], it was desirable to present early results with the new prosthesis in order to avoid potential errors. Schierholz et al [26] have raised concerns that free silver ions may precipitate in albumin-containing environments (e.g., hematoma), leading to concentrations that are too low for bactericidal effects to be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive results of these earlier studies made routine use of silver-coated megaprostheses possible in our department. Since negative results with silver-coated devices have also been reported in the literature [10,11,25], it was desirable to present early results with the new prosthesis in order to avoid potential errors. Schierholz et al [26] have raised concerns that free silver ions may precipitate in albumin-containing environments (e.g., hematoma), leading to concentrations that are too low for bactericidal effects to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological side effects in patients receiving a silver-coated tumor endoprosthesis have been excluded in previous studies [9], and high antimicrobial activity of the silver coating has been demonstrated in a rabbit model [4]. However, a lack of effectiveness has also been reported [10,11]. The aim of the present study was therefore to compare the actual infection rate among patients with titanium tumor prostheses with the infection rate in patients in whom silver-coated prostheses were implanted in the proximal femur and proximal tibia.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic silver provides antimicrobial activity and the cuff provides a mechanical barrier to the migration of microorganisms along the external surface of the catheter. In studies of catheters left in place 120 days, the cuff failed to reduce the incidence of CRBSI [94,95]. Two other studies of short-term catheters could not demonstrate efficacy because of the minimal number of CRBSIs observed [93,96].…”
Section: Antimicrobial/antiseptic Impregnated Catheters and Cuffsmentioning
confidence: 99%
“…Reason for exclusion Geffers, 2003 102 Review of the methodological quality of the trials available in this area of research Mermel, 2000 103 All CRBSI preventive strategies Zurcher, 2004 106 Compared single and multilumen CVCs Saint, 2000 40 Clinical and economic consequences of nosocomial CVC-related infection Bambauer, 2004 101 Narrative overview Raad, 1999 104 Narrative overview Sherertz, 2004 105 Narrative overview 3 Maki, 1988 75 Cuff vs non-cuffed ✓ ✓ Flowers, 1989 108 Cuff vs non-cuffed ✓ ✓ Kamal, 1991 109 In-house preparation ✓ ✓ ✓ of AI-CVCs Groeger, 1993 110 Cuff vs 2nd cuff ✓ ✓ Babycos, 1993 72 ✓ Bach, 1994 98 Interim results ✓ ✓ Ramsay, 1994 99 Interim results ✓ ✓ Dahlberg, 1995 111 Silver cuff vs non-cuffed ✓ Goldschmidt, 1995 112 German ✓ ✓ ✓ Smith, 1995 113 Cuff vs non-cuffed ✓ ✓ Trazzera, 1995 114 Non-RCT ✓ ✓ Appelgren, 1996 115 Standard CVC vs ✓ heparin-bonded CVC Bach, 1996 53 In-house preparation ✓ ✓ of AI-CVCs reviewed. Below are some of the issues that were raised by the reviews.…”
Section: Appendixmentioning
confidence: 99%